Thermische Untersuchungen an Laser-aktivierten Leuchtstoff-Systemen mit dynamischer Leuchtdichteverteilung - Vogl, Maximilian (Spektrum der Lichttechnik, 2023)
The simulation of ceramic phosphors by means of the diffusion approximation of the radiation transport equation is extended from rotationally symmetrical cases to general, three-dimensional problems. The phosphor is simulated with the diffusion approximation for a temporal and spacial variable laser light source for the first time. Therefore, different laser light sources are being compared to evaluate, which one of the alternatives is best suited for the intended use in an automotive head lamp.